1986
DOI: 10.1136/vr.119.6.151
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes in the pericardium and meninges of cattle associated with Clostridium chauvoei

Abstract: Twenty-nine cases of Clostridium chauvoei infection in cattle were investigated over a two-year period. Fourteen had lesions of myositis only, eight had lesions of both myositis and fibrinous pericarditis, six had lesions of fibrinous pericarditis only and one had lesions of purulent meningitis only. Cl chauvoei was identified in all the lesions using the fluorescent antibody technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…According to UZAL et al (2003), germination of C. chauvoei in the myocardium is commonly associated with stress during vaccination. Specifically, in the present report, the age of the affected animal (9 months) is consistent with other reports of clostridial myocarditis (MALONE et al, 1986;UZAL et al, 2003;ASSIS et al, 2010).…”
Section: O Objetivo Deste Estudo Foi Relatar Um Caso De Miocardite CLsupporting
confidence: 81%
See 4 more Smart Citations
“…According to UZAL et al (2003), germination of C. chauvoei in the myocardium is commonly associated with stress during vaccination. Specifically, in the present report, the age of the affected animal (9 months) is consistent with other reports of clostridial myocarditis (MALONE et al, 1986;UZAL et al, 2003;ASSIS et al, 2010).…”
Section: O Objetivo Deste Estudo Foi Relatar Um Caso De Miocardite CLsupporting
confidence: 81%
“…Comparatively, the macroscopic and microscopic lesions described here were similar to those described previously by MALONE et al (1986) and relatively different from those described by UZAL et al (2003), who reported a diffuse necro-hemorrhagic myocarditis not associated with fibrino-necrotic pleuritis.…”
Section: O Objetivo Deste Estudo Foi Relatar Um Caso De Miocardite CLsupporting
confidence: 68%
See 3 more Smart Citations